2002
DOI: 10.1063/1.1469666
|View full text |Cite
|
Sign up to set email alerts
|

The Meyer–Neldel rule for a property determined by two transport mechanisms

Abstract: We propose that the Meyer-Neldel rule ͑MNR͒ arises naturally for a quantity where both an intrinsic process as well as a process involving impurities contribute. The strength of the latter depends solely on the density of the impurities. This leads to a spread in the apparent activation energy of the measured quantity and the observation of the MNR, even though the intrinsic processes have fixed activation energies. A consequence of the MNR is the occurrence of a temperature T MN where a measured parameter is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…For example, in amorphous silicon, the rule has been attributed to the temperature dependence of Fermi energy and to the diminution of the band gap with increases of temperature [14]. Widenhorn [15] and coworkers propose that the MN rule arises for a thermally activated property when both, intrinsic and extrinsic processes involving impurities, contribute. In this case the property is considered the sum of two thermally activated mechanisms which can cause a spread in the effective activation energy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in amorphous silicon, the rule has been attributed to the temperature dependence of Fermi energy and to the diminution of the band gap with increases of temperature [14]. Widenhorn [15] and coworkers propose that the MN rule arises for a thermally activated property when both, intrinsic and extrinsic processes involving impurities, contribute. In this case the property is considered the sum of two thermally activated mechanisms which can cause a spread in the effective activation energy.…”
Section: Discussionmentioning
confidence: 99%
“…In context of multiple trapping dominated charge transport it was associated with the presence of the exponential distribution of traps. [12][13][14][15][16] Widenhorn et al 17 argue that the MNR arises for an arbitrary system where an intrinsic rate process as well as an impurity related process both contributes while Yelon and Movaghar 18 suggest that the MNR is obeyed when a thermally activated process requires a large number of individual excitations which increase the entropy. Recently, Emin 19 advanced an adiabatic polaron hopping model that considers carrierinduced softening of the vibrations upon electron motion and showed that this brings up the MNR.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that such a change in the activation energy can explain the observation of the MNR. 11 The origin of the shift in the activation energy with changing temperature for dark current in a CCD will be discussed in the next section.…”
Section: The Meyer-neldel Rule For Dark Current In a Ccdmentioning
confidence: 99%